Pengaruh Budaya Organisasi Terhadap Penerapan Balanced scorecard - Hamdani Hamdani; Saipul Arni Muhsyaf; Siti Aisyah Hidayati (Universitas Mataram, 2023)
An organizational culture that supports change, innovation, collaboration, and a focus on results can strengthen BSC implementation. On the other hand, a culture that resists change, rigid hierarchies, or lacks respect for performance measurement can be barriers to implementing BSC effectively. This study aims to analyze the effect of human resources, information technology, management accounting systems on managerial performance with environmental uncertainty as moderating. The research population is all hotel in Mataram City as many as 133 hotel. The research sample was taken as many as 100 hotel. The data analysis method in this study is SEM-PLS with the help of the Smart PLS version 3.0 program.The results of the study state that partially, human resources, Information Technology has a positive effect on managerial performance and Management Accounting System does not have a positive effect on managerial performance. Then, environmental uncertainty strengthens the influence of Information Technology and Management Accounting Systems on the managerial performance of pharmacies. Furthermore, environmental uncertainty weakens the influence of Human Resources on the managerial performance of pharmacies. The implications of this research can theoretically improve and add new theories, practically as a guide in improving managerial performance and as a policy consideration for policymakers in issuing pharmacy regulations in Mataram City.